ANALISIS TINDAK TUTUR ILOKUSI PADA PEMBELAJAR BAHASA JEPANG DALAM KLUB BAHASA NIHONGO DE SHABEROUKAI DI MEDAN - Nasution , Laraiba; Sonaria Hasibuan, Annalisa (Universitas Negeri Jakarta, 2019)
This study examines the analysis of illocution speech acts in Japanese language learners in the